A Comprehensive Review of Alternative Medicine: Biological Plausibility, Testability, Repeatability, and Effectiveness - Mohd. Wasiullah; Piyush Yadav; Shivanand Yadav; Sumit Kumar Yadav (International Journal of Membranes, 2025)
Alternative medicine, encompassing practices, such as acupuncture, herbal remedies, homeopathy, chiropractic care, Ayurveda, and Traditional Chinese Medicine (TCM), has gained global popularity as patients seek non-conventional healthcare solutions. Despite its widespread use, scientific evaluation of its biological plausibility, testability, repeatability, and effectiveness remains a significant challenge. This review critically examines these four criteria to assess the validity and reliability of alternative therapies. Acupuncture demonstrates partial plausibility, with evidence suggesting its ability to modulate pain pathways, though the concept of qi lacks empirical support. Herbal medicine shows promise due to pharmacologically active compounds, yet variability in standardization hinders consistent results. Homeopathy faces significant criticism for its lack of biological plausibility, with its effects often indistinguishable from placebo. Chiropractic care provides limited benefits for musculoskeletal pain but lacks evidence for broader health claims. Similarly, Ayurveda and TCM are challenged by individualized approaches and pre-scientific frameworks, though certain herbs and practices show pharmacological potential. Testability is a recurring issue across modalities due to variability in protocols, reliance on anecdotal evidence, and patient-specific factors. The repeatability of results is often limited by inconsistent methodologies, product quality, and practitioner variability. Effectiveness is largely condition-dependent, with alternative medicine offering relief for chronic pain and stress but failing to consistently meet the rigorous standards of conventional medicine. This review underscores the need for rigorous scientific investigation to bridge the gap between traditional knowledge and modern medical paradigms, ensuring that alternative medicine can be integrated responsibly and effectively into healthcare systems.
Keywords: Acupuncture; Alternative medicine; effectiveness; herbal remedies; testability